Mindfulness-Based Stress Reduction adapted to pregnant women with psychosocial vulnerabilities - a randomized feasibility trial in a Danish hospital-based outpatient setting - Sine Skovbjerg; Michelle Kolls; Anette Kjærbye-Thygesen; Lone Overby Fjorback (Pilot and Feasibility Studies)
Abstract Background Supporting prenatal mental health in women with a preconception history of mental disorders or psychosocial vulnerability is important for a positive transition to parenthood. There is a need for more evidence-based and non-pharmacological mental health interventions in antenatal care. The primary objective of this trial was to evaluate the feasibility of prenatal MBSR, which is an adaption of Mindfulness-based stress reduction (MBSR). This to inform a randomized controlled trial. Methods/design The trial was conducted at an obstetric outpatient clinic at Copenhagen University Hospital, Amager and Hvidovre, Denmark. The outpatient clinic specializes in antenatal care for pregnant women with psychosocial vulnerabilities. Pregnant women were randomly assigned to an intervention group receiving prenatal MBSR or a waitlist control group. The primary outcome was the feasibility of a full-scale randomized controlled trial (RCT). Second, to examine trends in self-reported outcomes, i.e., mental well-being, perceived stress, anxiety, depression, decentering, reflective functioning, mindfulness, and self-compassion. Results Of 123 eligible women, 73 consented to participate (59.3%). The majority (75.3%) were nulliparous. The mean age was 30.7 (SD 4.7) years, and most participants were employed (74%) and living with a partner (93.1%) at the time of recruitment. The majority of participants had a history of one or more mental disorders. Most frequently depression or an anxiety disorder. For the intervention group (n = 37), 54.1% completed the prenatal MBSR program. The loss to follow-up was 56.8% for the intervention group (n = 21) and 50% for the waitlist control group (n = 18). For the secondary outcomes, all variables except for reflective functioning pointed in the expected direction, e.g., improved mental well-being, reduced mental distress, and more self-compassion. Conclusions The results from this trial suggest that prenatal MBSR is a feasible intervention for a clinical setting, supporting the conduct of an RCT. Strategies for improving adherence and reducing the extent of missing data would be advisable in a future RCT. Overall, there is a need for more evidence-based and non-pharmacological interventions addressing prenatal mental health. Results from a future RCT could thus be of relevance to antenatal care. Trial registration NCT04571190, September 30, 2020 (ClinicalTrials.gov).